Improvement of plant regeneration efficiency using polyamines for double haploid production in wheat (Triticum aestivum) - GOYAL, PRINKA; THIND, S K; SRIVASTAVA, PUJA; SHARMA, ACHLA (The Indian Journal of Agricultural Sciences, 2022)
Polyamines are low molecular weight nitrogen containing compounds present in all living organisms. These are considered to be a new class of plant hormones, and play a positive role in plant growth and developmental processes including cell division, in vitro organogenesis and somatic, and zygotic embryogenesis. In our study, three polyamines PUT, SPD and SPM were used alone and in combinations in plant regeneration medium for in vitro plant regeneration from embryo developed through wheat × maize cross for double haploid production in wheat. Usually, these embryos have low regeneration efficiency but polyamines addition alone and in combinations in plant regeneration medium enhanced plant regeneration frequency as compared to control. Lower concentration of polyamines (1 and 2 ppm) has been found to be effective as compared to higher concentration (5 ppm). The polyamine concentration 1 ppm found to be promising concentration to improve plant regeneration. The combination of polyamines PUT+SPD (0.5 ppm+0.5ppm) proved better than other combinations to enhance plant regeneration frequency. The combination of PUT+SPD+SPM (0.5 ppm + 0.25 ppm + 0.25 ppm) although reduced plant regeneration frequency but plants were more vigorous and healthy.